1983
DOI: 10.1111/j.1440-1681.1983.tb00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the Antihypertensive Effect of Captopril by the Opioid Receptor Antagonist Naloxone

Abstract: To test a possible role of endogenous opioids in the blood pressure (BP) and heart rate (HR) responses to the converting enzyme inhibitor captopril in man, nine normal subjects were given captopril (50 mg) or placebo with and without the opioid antagonist naloxone (0.2 mg/kg i.v.). Treatments were given in random order and under double-blind conditions. BP and HR were measured supine and after a 5 min head-up tilt to 60 degrees before, 90, and 360 min after captopril. BP and HR responses to Valsalva's manoeuvr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…In the present study in normal volunteers, naloxone did not alter captopril-induced changes in BP and Valsalva ratio. This is in contrast to previous studies (Millar et al 1983;Rubin et al 1984;Ajayi et al 1985b) where reversal of captopril induced changes in BP and HR was abolished by naloxone, but only after 60-90 min.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study in normal volunteers, naloxone did not alter captopril-induced changes in BP and Valsalva ratio. This is in contrast to previous studies (Millar et al 1983;Rubin et al 1984;Ajayi et al 1985b) where reversal of captopril induced changes in BP and HR was abolished by naloxone, but only after 60-90 min.…”
Section: Discussioncontrasting
confidence: 99%
“…Richter et al 1991) and thus possibly inhibiting sympathetic nerve stimulation, which could account for the absence of reflex tachycardia. Furthermore, attenuation of the antihypertensive effect of captopril by naloxone has been previously demonstrated (Millar et al 1983;Rubin et al 1984).…”
Section: Introductionmentioning
confidence: 95%
“…In dogs, 0.1 mg/kg naloxone reversed enalapril and enalaprilic acid inhibition of the vagal-stimulation pressor response (40). Co-administration of 0.2 mg/kg naloxone mitigated captopril-related decreases in systolic and diastolic blood pressure in healthy men (41). Another double-blind, placebo-controlled study of healthy men found that naloxone pretreatment with 10 mg followed by 2.46 mg/hr infusion eliminated captopril-induced systolic blood pressure drop (42).…”
Section: Discussionmentioning
confidence: 95%
“…Naloxone has been ineffective in reversing hypotension in other cases complicated by co-ingestants [464]. The mechanism may relate to antagonism of endogenous opioids [465]. Co-administration of 0.2 mg/kg naloxone mitigated captopril-related decreases in systolic and diastolic blood pressure in healthy volunteers [465].…”
Section: Naloxonementioning
confidence: 99%
“…The mechanism may relate to antagonism of endogenous opioids [465]. Co-administration of 0.2 mg/kg naloxone mitigated captopril-related decreases in systolic and diastolic blood pressure in healthy volunteers [465]. A placebo-controlled study of healthy men found that naloxone pretreatment with 10 mg followed by 2.46 mg/hour infusion precluded systolic blood pressure decrease induced by captopril (50 mg) [466].…”
Section: Naloxonementioning
confidence: 99%